Apoptotic and cytotoxic effects on human glioblastoma cell lines induced by essential oil Lavandula Augustifolia. Issue 1 (21st February 2020) - Chan, Siu‐Yee; Li, Yi; Poon, Wai‐Sang
Abstract: Aim: The challenge of treating glioblastoma has been the lack of curative treatment. This study aimed to identify an effective low dose of the essential oil from Lavandula angustifolia (EOla), within a short exposure time for inhibiting growth and inducing apoptosis in glioblastoma cells. Methods: Cell lines U‐87MG and U‐138MG were treated with diluted EOla (1:250 to 1:50) at 2, 4, 8 and 48 hours time points. The treated samples were compared with the negative control and DMSO vehicle control in MTT anti‐proliferation tests and flow cytometry cell sorting experiments. A positive control (DNase I) was included in the TUNEL imaging assay. Results: Our data consistently showed that diluted EOla started inducing apoptosis at 1:250 dilution in both U‐138MG and U‐87MG samples. Significant differences in cell viability between DMSO and EOla samples were found in U‐87MG, ( P = .02) and U‐138MG, ( P = .003) . Our flow cytometry results demonstrated that glioblastoma cells exposed to 1:100 diluted EOla for 4 hours had induced cell death in U‐87MG with 94.9% ± 2.6 apoptosis and 1.7% ± 2.2 necrosis; and in U‐138MG with 99% ± 3.3 apoptosis and 9.8% ± 3.1 necrosis. Conclusion: Unadulterated pure therapeutic grade EOla at the concentration of 1:100 dilution has been shown to induce predominantly apoptosis (>95%) with limited necrosis (1%‐10%).